Scaffold-Based Tissue Engineering Strategies for Osteochondral Repair - Fu, Jiang-Nan; Wang, Xing; Yang, Meng; Chen, You-Rong; Zhang, Ji-Ying; Deng, Rong-Hui; Zhang, Zi-Ning; Yu, Jia-Kuo; Yuan, Fu-Zhen (Frontiers in Bioengineering and Biotechnology, 2022)
Over centuries, several advances have been made in osteochondral (OC) tissue engineering to regenerate more biomimetic tissue. As an essential component of tissue engineering, scaffolds provide structural and functional support for cell growth and differentiation. Numerous scaffold types, such as porous, hydrogel, fibrous, microsphere, metal, composite and decellularized matrix, have been reported and evaluated for OC tissue regeneration in vitro and in vivo, with respective advantages and disadvantages. Unfortunately, due to the inherent complexity of organizational structure and the objective limitations of manufacturing technologies and biomaterials, we have not yet achieved stable and satisfactory effects of OC defects repair. In this review, we summarize the complicated gradients of natural OC tissue and then discuss various osteochondral tissue engineering strategies, focusing on scaffold design with abundant cell resources, material types, fabrication techniques and functional properties.